2010
DOI: 10.1038/hr.2010.2
|View full text |Cite
|
Sign up to set email alerts
|

Incremental predictive value of carotid intima–media thickness to arterial stiffness for impaired coronary flow reserve in untreated hypertensives

Abstract: Coronary microcirculation is disturbed in patients with arterial hypertension. Carotid intima-media thickness (IMT) and arterial stiffness are markers of subclinical atherosclerosis with prognostic significance. We investigated whether the combination of increased carotid IMT and arterial stiffness has a greater predictive value for the presence of impaired coronary flow reserve (CFR) than each index alone in never-treated hypertensives. We studied 110 untreated patients (age: 54.5±12 years) with newly diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…This correlation indicates that both CCAIMT and CAVI are associated with early atherosclerotic changes (arterial stiffness). 21,34 Carotid intima-media thickness is also a useful and non-invasive method to examine atherosclerosis and is associated with future stroke risk. 2,3,34 There were several limitations to this study.…”
Section: Arterial Stiffness and Silent Brain Infarct N Saji Et Almentioning
confidence: 99%
“…This correlation indicates that both CCAIMT and CAVI are associated with early atherosclerotic changes (arterial stiffness). 21,34 Carotid intima-media thickness is also a useful and non-invasive method to examine atherosclerosis and is associated with future stroke risk. 2,3,34 There were several limitations to this study.…”
Section: Arterial Stiffness and Silent Brain Infarct N Saji Et Almentioning
confidence: 99%
“…37 This result is in line with another study, which showed that arterial stiffness is an independent predictor of vascular health and coronary artery disease above and beyond intima-media thickness. 38 Arterial stiffness increases chronically with age, with the development of chronic conditions (for example, hypertension), and with the presence of vascular risk factors (for example, smoking). [39][40][41] These observations have prompted researchers investigating OSAcardiovascular interactions to study the role of OSA in increasing arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…6 This global approach to arterial function, 9 in addition to potentially solidifying the concepts elaborated in the study by Tzortis et al, 3 could further improve risk stratification for impaired CFR. Furthermore, it is interesting to consider that certain types of antihypertensive drugs improve CFR beyond what would be expected solely on the basis of a reduction in blood pressure.…”
mentioning
confidence: 93%
“…[4][5][6] Interestingly, aortic stiffness has an independent predictive role not only for all-cause mortality but also for coronary events. [4][5][6] Causal relationships explaining this role do exist, and the findings of Tzortzis et al 3 provide a link. Increased arterial stiffness increases the velocity of the incident and reflected pulse waves, which in turn shifts the pressure wave reflections from diastole to systole.…”
mentioning
confidence: 96%
See 1 more Smart Citation